Model for Early Detection of Breast Cancer in Low-Resource Areas: The Experience in Peru - Carolyn Bain (Journal of Global Oncology, 2018)
Purpose: Late-stage breast cancer detection should be something of the past; however, it is still all too common in low-resource areas, including Peru, where 57% of women diagnosed with cancer are diagnosed at stage III or IV disease. Early detection of breast cancer is feasible in low-resource semirural and rural areas where mammography is rarely accessible. Methods: PATH collaborated with Peruvian health institutions at local, regional, and national levels to design and implement a model of care for the early detection of breast cancer in Peru. The model includes training health promoters for community outreach, professional midwives in clinical breast exam, doctors to perform fine-needle aspiration biopsy sampling with ultrasound to triage, and patient navigators to ensure patients follow through with treatment. Results: In a northern region of Peru, 400 individuals, including health promoters, midwives, doctors, and volunteers, received early-detection training in two phases. In Peru, local health professionals continue to refine and improve methods and materials using locally available resources, and the Peruvian health information system now includes specific breast cancer detection categories. Despite challenges and limited resources, the model is effective, and partnership with government health administrations improves health systems and benefits the population. Conclusion: Given the absence of screening mammography, the public health challenge is to bring breast cancer early detection and diagnostic services closer to women’s homes and to ensure appropriate follow-up and care. The model is eminently transferable with appropriate adaptation and should now be tested in other settings within and outside of Peru.